Body Image And Nutrition Knowledge With Fast Food Consumption Habits for Student During A Pandemic - Arumdani, Evania Sekar; Muwakhidah, Muwakhidah; Kurnia, Pramudya; Setyaningrum, Zulia (Prosiding University Research Colloquium, 2022)
During the Pandemic Period, social restrictions were imposed so that student activities were carried out online which led to a decrease in physical activity. In addition, today's youth lifestyle is often consuming fast food because it is fast, practical and there are many fast food restaurants available around them. Knowledge of low nutrition can affect the habit of consuming fast food without paying attention to the nutritional content contained in it. The impact of excessive consumption of fast food can cause various nutritional problems, one of which is being overweight. Being overweight in adolescent girls causes adolescents to feel dissatisfied with their physical appearance and will lead to negative perceptions of their own bodies. This study aims to determine the relationship between body image (body image) and nutritional knowledge with fast food consumption habits in students of the Faculty of Health Sciences, University of Muhammadiyah Surakarta. The design of this research is observational with a cross sectional approach. The sampling technique used is Simple Random Sampling with a total sample of 113 people. Body image data was obtained from a body image questionnaire with the MBSRQ (Multidimensional Body-Self Relation Questionnaire) with a total of 32 questions and nutrition knowledge data obtained from a balanced nutrition knowledge questionnaire with a total of 20 questions, and data on fast food consumption habits obtained from the Food form. Frequency Questionnaire (FFQ) for the last 3 months. This research was conducted online using a Google form that was distributed through Whatsapp groups. Analysis of the relationship between variables using the Spearman Rank test. The perception of body image is included in the negative category, namely 92.9%, the level of nutritional knowledge is included in the good category, namely 72.6% and fast food consumption habits are included in the low category, namely 59.3%. Research subjects who have a negative body image and have fast food consumption habits in the high category are 41%, and research subjects who have good knowledge and have high fast food consumption habits are 41.5%. The results of this study indicate that there is no relationship between body image (p = 0.220) and nutritional knowledge (p = 0.740) with fast food consumption habits in students of the Faculty of Health Sciences, Muhammadiyah University, Surakarta.